Digital Neural Loops: Classification and Implications of Variation in Hand Surgery - Niumsawatt, Vachara; Rozen, Warren Matthew (Journal of Reconstructive Microsurgery, 2014)
Background The “neural loop” describes a digital artery passing through a digital nerve, after which both the structures progress distally to supply the digit. While rare, past descriptions refer to neural loops located around the common palmar digital arteries, with no reports of more distal loops.Methods We describe a case in which a distal neural loop was identified, with the ulnar proper palmar digital nerve (PPDN) to the long finger split, and reconstituted around the radial proper palmar digital artery (PPDA) to the ring finger. This variation was explored within the previously reported classification systems for such neural loops in the literature.Results Previously reported neural loops have been localized to the palm, without report of formation of a neural loop by the penetration of a PPDA. A new classification of neural loops is presented in this context on the basis of anatomical location.Conclusion This new model, of separating neural loop position into anatomical levels, provides more information to the hand surgeon when dissecting and raising vascular pedicles for flaps reconstruction.
Keywords: hand surgery; digital vessel; digital nerve; artery; nerve